Birth preparedness and complications readiness among women in disadvantaged rural districts of Ghana - Abraham Rexford Oduro; Maria Anyorikeya; Patrick Ansah; Samuel Oladokun; Ernest Maya Tei; Randy Oduro-Ayeh; Paul Welaga; Seli Deh (BMC, 2023)
Abstract Introduction Essentially all women and babies irrespective of their economic and social status should reach their full potential for health and well-being. The study assessed the readiness of mothers and their preparedness for birth across three disadvantaged rural districts in Ghana. Methods A multi-centre quantitative survey from January to December 2018 using a multistage sampling approach was employed. Using a structured questionnaire data from mothers attending antenatal and postnatal clinics in three main ecological zones of Ghana were collected. Women who provided informed consent were consecutively recruited until the sample size was achieved. For categorical data, summary tables, proportions and percentage are presented. Multivariate logistic regression analysis determined the effect of selected characteristics on birth preparedness. Ethics approval was obtained from the Navrongo Health Research Centre. Results A total of 1058 mothers were enrolled: 33.6%, 33.4% and 33.0% respectively from the Ada west, Upper Denkyira west and Builsa south districts. About 94% of the women had prior knowledge of birth preparedness. Approximately 22.6% (95%CI 20.1, 25. 2) of the mothers were assessed to have poor birth preparedness: 8.0% in Builsa south, 27.8% in Ada west and 31.7% in Upper Denkyira west. Prenatal and postnatal data showed no statistically significant difference in poor preparedness (21.9% vs 23.3%; p-value > 0.05). Maternal age, employment status, religious affiliation and parity were not associated with birth preparedness (p-value > 0.05). Area of study (P < 0.001), educational level (P < 0.016), marital status (p < 0.001) and antenatal contacts (< 0.001) were significantly associated with birth preparedness. Conclusions As an important safe motherhood strategy woman should plan their pregnancy and birth well to reduce maternal and neonatal mortality. Policy initiatives should take into consideration area of residence, education, marital status and antenatal contacts of women.